Development of insole sensing system for feet analysis - Koo, Hui Min (2010)
This report presented a insole sensing system for feet analysis for people with foot abnormalities or injuries. This project will consists of both hardware and software implementation. Seven pair of pressure sensors (FlexiForce® Force Sensors, USA) was inserted into the shoe for the measurement of force up to 1000 Ibs. Together with the pressure sensors, ultrasonic sensors is incorporated with the shoe by the side to measure the distance between foots. The shoe is specially designed to cater ease of servicing and positioning of sensors is carefully carried out as it influence the accuracy in acquiring data. All the data collected will be send to a main board through programmed microcontrollers. Data include the pressure exerted by the subject in volts and the distance measured in meters. Bluetooth technology is employed in this case to send the data wirelessly to a computer. Matlab software is used to design the feet analysis system. Subject will wear the insole sensing shoe and performed walking on a flat ground. Results is collected and analyze for possibilities of abnormalities or injuries. The system can also track the pressure exertion of the subject with respect to a nominal value. After each run of the test, information will be stored as well for future references. With the good estimation accuracy, inexpensive cost and user-friendly system, insole sensing system is readily available to be implanted in shoe for estimation and monitoring of foot conditions together with Matlab system for analysis.